Characterization of Fe-Mo alloy obtained by electroplating (Research, Society and Development, 2020)
In this work, an experimental design associated with the response surface methodology (RSM) technique was used, to evaluate the effect of deposition parameters, current density, and pH of the electrolytic bath, on the properties of Fe-Mo coatings. obtained by electrodeposition. The morphological characteristics of the coatings were evaluated by SEM and the proportional ratio of the deposited metals was evaluated by EDX. The corrosion resistance of the alloys in a corrosive medium containing chloride ions (3.5 %, NaCl) was evaluated using the techniques of Potentiodynamic Polarization (PP) and Electrochemical Impedance Spectroscopy (EIS). The results of chemical composition showed that iron was electrodeposited in a greater proportion in all experiments, confirming its inducing effect on the molybdenum deposition mechanism. The corrosion results showed that the coatings obtained in the experimental conditions of 60 mA/cm² and pH 6 presented the best anticorrosive performance among the evaluated systems. The experimental optimization showed that the pH variable of the electrolytic bath had a greater influence on the results of the chemical composition of the alloy compared to the current density variable. Therefore, the results presented here confirm the importance of using experimental optimization techniques applied to obtain coatings obtained by electrodeposition with controlled properties for specific applications.